2014
DOI: 10.1186/s12302-014-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of evidence that the organophosphorus insecticide chlorpyrifos is a potential persistent organic pollutant (POP) or persistent, bioaccumulative, and toxic (PBT)

Abstract: A number of chemicals, including several organochlorine pesticides, have been identified as persistent organic pollutants (POPs). Here, the properties of chlorpyrifos (CPY; CAS No. 2921-88-2) and its active metabolite, chlorpyrifos oxon (CPYO; CAS No. 5598-15-2), are assessed relative to criteria for classification of compounds as persistent, bioaccumulative, and toxic substances (PBTs). The manufacture and use of POPs are regulated at the global level by the Stockholm Convention (SC) and the UN-ECE POP Protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 74 publications
(143 reference statements)
0
15
0
Order By: Relevance
“…WoE offers a structured and transparent approach to risk assessments and is of particular value for assessments involving a number of different lines of evidence. To date, WoE has been used infrequently in a formal and quantitative sense for risk assessment in relation to persistent organic pollutants (POP) and long-range transport (LRT), with the possible exception of the Giesy et al (2014) evaluation of persistent, bioacumulative, and toxic (PBT) properties of chlorpyrifos.…”
mentioning
confidence: 99%
“…WoE offers a structured and transparent approach to risk assessments and is of particular value for assessments involving a number of different lines of evidence. To date, WoE has been used infrequently in a formal and quantitative sense for risk assessment in relation to persistent organic pollutants (POP) and long-range transport (LRT), with the possible exception of the Giesy et al (2014) evaluation of persistent, bioacumulative, and toxic (PBT) properties of chlorpyrifos.…”
mentioning
confidence: 99%
“…Our findings, in soil exposed to natural illumination, suggesting that toxicity to soybean seed germination abates by the sixth week (as no significant differences were observed due to the pesticides concentrations in the sixth week after initial application), are not far-fetched. Glesy et al, [27] in a review on evidence for classification of chlorpyriphos and its metabolitechlorpyriphos oxon as a: persistent organic pollutant (POP), and persistent bioaccumulative and toxic (PBT), concluded that there was not sufficient justification for the classification of chlorpyriphos as a POP or PBT. It appears our results on seed germination of soybean, add to, rather than subtract from their position; keeping in mind that manufacturer recommended preparations were used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, iPSCs have advantages in both directions: they can be reprogrammed from patients, and thus obtain the susceptible genotype; reversely, they can be differentiated into many cell types including neuronal cells and represent the process of neural development although the differentiation methods are still different between laboratories. A recent study, for instance, using iPSC found that chlorpyrifos, a potential POP [ 210 ], downregulated of neurogenesis genes during neural differentiation process [ 211 ]. Genome editing has been in research for decades and used productively; epigenome editing, on the other hand, is just in its beginning.…”
Section: Conclusion and Perspectivementioning
confidence: 99%